Some considerations about the assessment of evaluative instruments and the interpretation of their results. - Luis Alberto Corona Martínez (Medisur)
The usefulness and conveniences of the usage of the difficulty and discrimination indexes in the appraisement and elaboration of evaluative instruments are analysed in this paper. These indexes have been designed to be applied in the so called tests of relative criteria that are not used in our context in which tests with reference to a criteria are applied. The importance of other qualities in tests such ad pertinence, validity of the content, objectivity/ objectiveness , and amplitude are also insisted on and the quality of the assessment starting from a curve of distribution of qualifications in different categories of symbols is a questionable aspect too.